Fórmula : x= -b ± √ b
² - 4ac
2a
1) 7x2 + 21x - 28 = 0
ax2
+bx +c = 0
a = 7
b = 21
c = -28
= -
(21) ± √ (21) 2 - 4 · 7 (-28)
2(7)
= - 21 ± √ 441 – (-784)
14
= -21± √ 1225
14
= - 21 ± 35
14
= -21 + 35 = 1
14
= - 21 – 35 = - 4
14
X1 = 1
X2 = -4
2) − x2
+ 6x − 9 = 0.
ax2
+bx +c = 0
a = −1
b =
6
c = −9
= -6 ± √ 62 – 4 (-1) (-9)
2(-1)
= -6 ± √ 36 – 36
-2
= -6 ± √ 0
-2
-6 = 3
-2
3) 2x2 – 7x + 3 = 0
ax2
+bx +c = 0
a = 2
b = 7
c = 3
= 7 ± √ 72 – 4 ·2·3
4
= 7 ± √ 49 – 24
4
= 7 ± √ 25
4
= 7 ± 5
4
= 12 = 3
4
2 = 1
4 2
x1 = 3
x2 = 1/2
4) x2 – 7x + 10 = 0
ax2
+bx +c = 0
a = 1
b = 7
c =
10
= 7
± √ 72 – 4 · 10
2
= 7 ± √ 49 – 40
2
= 7 ± √ 9
2
= 7 ± 3
2
= 10 = 5
2
= 4 = 2
2
x1 = 5
x2 = 2
5) x 2 - x = 0
ax2
+bx +c = 0
a = 1
b = - 1
c = 0
x= -b ± √ b ² - 4ac
2ª
= - (-1) ± √ (-1)
2 – 4· 1· 0
2·1
= 1 ± √ 1 – 0
2
= 1 ± √ 1
2
= 1 ± 1
2
= 1+1 = 1
2
= 1-1 = 0
2
X1 = 1
X2 = 0
No hay comentarios:
Publicar un comentario